‘Remedies to cure the diseases or ill-affections of the Eares, Eies, Nose and Mouthe.’ Punctuation in London, Wellcome Library, MS. 676. - Linehan Gómez, Sinéad (My University, 2023)
Punctuation is an essential component of the written text, due to their shared history these two elements are bound (Parkes 1992, 1). Both modern and medieval punctuation are essentially of a syntactic structure, marking the grammatical system of the written word. Anyhow, the medieval punctuation was also ‘to a great extent rhetorical’ so as to underscore ‘the structure of the text’ for a meaningful reading aloud (Derolez 2003, 185). Parkes states how ‘new conventions’ emerged to help the readers to ‘extract the information conveyed’ in the written text (1992, 1). However, the 6th century marked the beginning of the development of the punctuation system as the written text came to be preferred ‘for silent reading which subsequently became established as the norm’ (Parkes 1992, 1). The subject of study of the present paper is the English recipe book housed in London, Wellcome Library, MS. 676. The title of this volume is ‘Remedies to cure the diseases, or ill affections of the Eares, Eies, Nose and Mouthe’ and it is dated ‘In Dei Nomine feliciter incipit 1607’. The volume offers four different sections relating the different parts of a person’s head, nevertheless, the first part additionally includes six chapters treating ‘diseases of the heade, haire, & face’. In order to display this manual in orderly fashion, the scribe of this volume adopted a wide range of punctuation symbols. In light of this, the objective of this paper is threefold: a) to classify the marks of punctuation in the witness; b) to analyse the uses and functions of the different marks of punctuation in view of context; and c) to discern whether the text was conceived by the scribe in terms of a grammatical or a rhetorical rationale of punctuation.
Keywords: Inglés moderno - Gramática; Inglés moderno - Ortografía; Punctuation; Manuscript; Medicine; Comma; Periodus